Agrobacterium-mediated genetic transformation of a tropical elite maize line - Souza, Rafaeli Aparecida Vieira de; Alves, Meire de Cássia; Carneiro, Newton Portilho; Barros, Beatriz de Almeida; Borém, Aluízio; Carneiro, Andréa Almeida (Crop Breeding and Applied Biotechnology, 2016)
The efficiency of maize transformation mediated by Agrobacterium tumefaciens is influenced by various factors. The aim of this study was to test the effect of different concentrations of N6 salts (50% - half strength, and 100% - full strength) in the infection and cocultivation media on genetic transformation efficiency of the L3 tropical elite maize line. Immature embryos were transformed via A. tumefaciens harboring the binary vector pTF102 containing the genes uidA and BAR under control of the CaMV35S promoter. The efficiency of the transgenic events produced was 3% for full strength and 1.1% for half strength N6 salts. Although under a lower concentration of salts, GUS expression was stronger; under this concentration, regeneration was less efficient. Thus, the results showed that the presence of 100% N6 salts in the infection and cocultivation media favored genetic transformation of the L3 maize inbred line mediated by A. tumefaciens.
O artigo não contém resumo em português
Keywords: Immature embryos; Salt concentration; Somatic embryogenesis; Zea mays